ANALISIS NILAI PENDIDIKAN KARAKTER SATUA BALI I LACUR DALAM PEMBENTUKAN BUDI PEKERTI SISWA SD - Ida Bagus Yoga Swadnyana; Made Wahyu Jayanthi; Ni Putu Dian Pita Yanti; Ni Kadek Ginantri Setiari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the character education values contained in the Balinese satua (traditional folktale) entitled "I Lacur" and their relevance to the formation of elementary school students' moral character. The research uses a qualitative descriptive method with a literary study approach. Data were collected through document study by reading, noting, and analyzing the content of the satua "I Lacur" systematically. The results show that the satua "I Lacur" contains at least six dominant character education values, namely: (1) religious values; (2) honesty; (3) perseverance and hard work; (4) social care; (5) responsibility; and (6) humility. These values are embedded through narrative elements such as characters, plot, and moral messages in the story. The satua "I Lacur" is relevant as a local wisdom-based learning medium to strengthen the character of elementary school students because it contains moral messages that are contextual, culturally rich, and easily internalized by children. This study contributes to the development of character education based on Balinese local wisdom in elementary school contexts, especially in supporting the implementation of the Merdeka Curriculum.